How the Cooperative Extension Service Uses Television - Carole S. Fromer (Journal of Applied Communications, 1979)
A 24-item questionnaire was sent to Extension communicators in 49 states to determine the extent to which portable video equipment is used by Extension personnel, and how they evaluate its effectiveness.